2001
DOI: 10.4049/jimmunol.166.9.5763
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Are a Major Source of Nitric Oxide-Derived Oxidants in Severe Asthma: Characterization of Pathways Available to Eosinophils for Generating Reactive Nitrogen Species

Abstract: Eosinophil recruitment and enhanced production of NO are characteristic features of asthma. However, neither the ability of eosinophils to generate NO-derived oxidants nor their role in nitration of targets during asthma is established. Using gas chromatography-mass spectrometry we demonstrate a 10-fold increase in 3-nitrotyrosine (NO2Y) content, a global marker of protein modification by reactive nitrogen species, in proteins recovered from bronchoalveolar lavage of severe asthmatic patients (480 ± 198 μmol/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
225
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(246 citation statements)
references
References 83 publications
13
225
1
4
Order By: Relevance
“…[42]. These results support the hypothesis of a difference in eNO concentration mediated by cell recruitment, in particular that of eosinophils with a T helper 2 pattern of cytokine activation (IL-4, IL-5) [43,44]. Nevertheless, other studies [45][46][47] have found a close pathophysiologic resemblance between atopic and non-atopic asthma in terms of both bronchial inflammatory cell recruitment and circulating factors.…”
Section: Discussionsupporting
confidence: 76%
“…[42]. These results support the hypothesis of a difference in eNO concentration mediated by cell recruitment, in particular that of eosinophils with a T helper 2 pattern of cytokine activation (IL-4, IL-5) [43,44]. Nevertheless, other studies [45][46][47] have found a close pathophysiologic resemblance between atopic and non-atopic asthma in terms of both bronchial inflammatory cell recruitment and circulating factors.…”
Section: Discussionsupporting
confidence: 76%
“…ing exposure to nitrating oxidants such as peroxynitrite/ peroxycarboxynitrite or peroxidase-mediated reactive nitrogen species. 14,37 Although the oxidative modifications monitored only represent a subfraction of total oxidative insults experienced by epithelial cell MnSOD within asthmatic airways, the quantification of this diverse array of distinct oxidative modifications provides insight into the potential degree of SOD functional impairment from oxidative processes. Given that there are 10 tyrosine residues per monomer and 4 monomers form an active Mn-SOD tetramer, if modification of only 1 tyrosine per MnSOD tetramer is sufficient to affect activity, then the observed cumulative modification burden of 1.13 to 1.73 mmol/mol tyrosine in isolated MnSOD predicts up to a 6% loss of MnSOD activity in these mild asthmatics.…”
Section: Nitration and Oxidation Of Mnsod In Asthmatic Airway Epithelmentioning
confidence: 99%
“…Although nonspecific events related to increased levels of reactive oxygen and nitrogen species in the asthmatic airway have been postulated to lead to epithelial cell loss, the precise mechanisms of effect are unknown. [12][13][14][15] In general, the human lung has an effective, well-integrated antioxidant system to combat reactive oxygen species and reactive nitrogen species injury, 12 however, the respiratory tract antioxidant capacity is impaired in asthma. 16 -18 Activity of superoxide dismutase (SOD) is lower in asthmatic lungs as compared to healthy controls, and decreases further during an asthmatic attack.…”
mentioning
confidence: 99%
“…Even though biological nitration yields are relatively low (100 -500 mol of nitrotyrosine/mol of tyrosine under inflammatory conditions) (2), they are an established marker for the extent of the production of nitric oxide ( ⅐ NO) 1 -derived reactive species during both physiological and pathological conditions. Cumulative protein tyrosine nitration, manifesting through multiple mechanisms, may be actively involved in the onset and/or progression of various diseases with an inflammatory component and associated with increased levels of reactive oxygen species and ⅐ NO (1,(3)(4)(5)(6)(7). Cumulative protein tyrosine nitration may also be involved in the pathogenesis of acute pathological conditions such as ischemia-reperfusion (8,9).…”
mentioning
confidence: 99%